E-strategy adoption and implementation: Re-examining the concept - Abdullah, Shahmir Sivaraj; Abdullah, Haim Hilman (Academy for Global Business Advancement (AGBA), 2015)
The majority of e-business solutions have focused on individual business improvement programs and strategies (Turban & King, 2012; Cunningham, 2002).Hamel (2002) cites an example where this new approach has both worked and at the same time created disruption within an industry whilst referring to Charles Schwab and Fidelity (both are American financial institutions) have changed the manner which customers deal with their savings resulting in mainstay US banks losing almost half of their market share to new online business models such as them.Robert and Racine (2001) conclude that there is a gap between convention and practice in this new area of commerce.They contend that in order for firms to transform from a conventional business model to an e-business model which is highly dependent on the Internet, firm‘s need to understand how IT systems are developed and deployed. Unfortunately, to most CEO‘s this is foreign terrain and the primary area of resource allocation is delegated to a project team with the mandate to develop a miracle plan (Robert and Racine, 2001).